Autism risk gene Cul3 alters neuronal morphology via caspase-3 activity in mouse hippocampal neurons - Xia, Qiang-qiang; Singh, Anju; Wang, Jing; Xuan, Zhong Xin; Singer, Jeffrey D.; Powell, Craig M. (Frontiers in Cellular Neuroscience, 2024)
Autism Spectrum Disorders (ASDs) are neurodevelopmental disorders (NDDs) in which children display differences in social interaction/communication and repetitive stereotyped behaviors along with variable associated features. Cul3, a gene linked to ASD, encodes CUL3 (CULLIN-3), a protein that serves as a key component of a ubiquitin ligase complex with unclear function in neurons. Cul3 homozygous deletion in mice is embryonic lethal; thus, we examine the role of Cul3 deletion in early synapse development and neuronal morphology in hippocampal primary neuronal cultures. Homozygous deletion of Cul3 significantly decreased dendritic complexity and dendritic length, as well as axon formation. Synaptic spine density significantly increased, mainly in thin and stubby spines along with decreased average spine volume in Cul3 knockouts. Both heterozygous and homozygous knockout of Cul3 caused significant reductions in the density and colocalization of gephyrin/vGAT puncta, providing evidence of decreased inhibitory synapse number, while excitatory synaptic puncta vGulT1/PSD95 density remained unchanged. Based on previous studies implicating elevated caspase-3 after Cul3 deletion, we demonstrated increased caspase-3 in our neuronal cultures and decreased neuronal cell viability. We then examined the efficacy of the caspase-3 inhibitor Z-DEVD-FMK to rescue the decrease in neuronal cell viability, demonstrating reversal of the cell viability phenotype with caspase-3 inhibition. Studies have also implicated caspase-3 in neuronal morphological changes. We found that caspase-3 inhibition largely reversed the dendrite, axon, and spine morphological changes along with the inhibitory synaptic puncta changes. Overall, these data provide additional evidence that Cul3 regulates the formation or maintenance of cell morphology, GABAergic synaptic puncta, and neuronal viability in developing hippocampal neurons in culture.